Sprachen und Bildungspolitik in Algerien - Yamina, Hamida (Stellenbosch Papers in Linguistics Plus, 2012)
Abstract: Languages like German, Spanish and Italian that are taught at tertiary education institutions, currently have become more significant in Algeria than is generally assumed. The continuing expansion of these languages at tertiary level will gradually contribute to a resolution in the battle for status between French and English in language planning debates. This paper considers which parties currently oppose French and promote English as the first foreign language (FL1), what the reasons are for attempting to establish English as FL1 at primary schools, why such an endeavour is doomed from the onset, and how an FL3, like German, may benefit from this state of affairs. Attached to this, the status of indigenous lanuages, like Algerian and Berber are considered in the complex plurilinguistic environment where “arabicization” is an issue. The paper topicalises linguistic and didactic consequences of such considerations, specifically concerning plurilingualism at primary school level and in academia. Keywords: Algeria, education policy, language conflict, mother tongue, second language, foreign language Schlüsselbegriffe: Algerien, Bildungspolitik, Sprachkonflikt, Muttersprache, Zweitsprache, Fremdsprache